Whole-body vibration and its effects on electromechanical delay and vertical jump performance - Stevenson, D. L. (2005)
The purpose of this study was to determine the effects of whole-body vibration on electromechanical delay and vertical jump performance. Twenty college aged subjects participated in 10 intervals of whole-body vibration (WBV) at a frequency of 26 Hz and amplitude of 5 mm. Each interval consisted of 60 s of WBV in a half-squat followed by 60 s of rest. After 5 intervals, subjects had 6 min of rest before the final 5 intervals. Each subject also participated in the control which included the same 10 intervals in a half-squat without the WBV. Tests were conducted to assess electromechanical delay (EMD) and vertical jump at baseline, during the 6 min rest period and immediately after the treatment and control. EMD was measured using tibial nerve stimulation and a force plate. EMD was recorded as the lag time between the initiation of gastrocnemeus stimulation and plantar flexion force production. Vertical jump was measured using a force plate and subjects’ flight time. The factorial ANOVA results showed no differences between groups, the control and WBV treatment, for both EMD (F (2, 38) = 1.385, p = 0.263) and vertical jump (F (2, 38) = 0.040, p < 0.96). The WBV treatment protocol chosen had no effect on vertical jump. These results suggest that WBV, using this protocol, is not effective for acute vertical jump or EMD enhancement. Also, since there was no effect on EMD, this suggests that the WBV treatment did not enhance muscle spindle sensitivity.